The academic and Non-Academic Factors Related to Students' Failing Subject or Attrition at the Department of Education at the School of Arts and Sciences of the University of El Salvador, Semester I-2000 - López Castillo, Sonia Guadalupe (Universidad de El Salvador, 2002)
Imídeo G. Nérici (1985) points out in his book, Hacia una Didáctica General Dinámica, that university teaching should avoid four things. First university studies should not only aim to prepare students to pass exams. Second, university students should not limit themselves to just take notes and then memorize them. Third, university students should neither play passive roles nor limit themselves to know just what the teacher gives them. Fourth, university students should not be kept away from the problems their community and country faces.